2016
DOI: 10.1002/aqc.2700
|View full text |Cite
|
Sign up to set email alerts
|

Combining ex situ and in situ methods to improve water quality testing for the conservation of aquatic species

Abstract: 1.Determining whether water quality is suitable is an important part of managing aquatic species for conservation, although it is often challenging to achieve. Past approaches have largely consisted of tests exposing individuals to artificial solutions, or field studies that examine the effect of a subset of water quality parameters on the distribution or abundance of a species.2. Owing to the complex nature of water chemistry in natural systems, which is difficult to replicate using laboratory studies or to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 30 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Summary of the main works presented in this research, summarizing the species studied, the location of the study, which pesticides were found, and the effects identified by the respective researchers. The environments used for the in situ experiments involved environments intended for general agricultural cultivation (Orton & Routledge 2011;Sparling et al, 2014), fruit orchards (Rosenbaum et al, 2012), rice cultivation (Attademo et al, 2014), soybean (Agostini et al, 2020;Dyck et al, 2021), maize and sorghum (Dyck et al, 2021), in addition to industrial use areas (Pollard et al, 2016) and water bodies with controlled spraying of pesticides (Thompson et al, 2004;Wojtaszek et al, 2005;Edge et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Summary of the main works presented in this research, summarizing the species studied, the location of the study, which pesticides were found, and the effects identified by the respective researchers. The environments used for the in situ experiments involved environments intended for general agricultural cultivation (Orton & Routledge 2011;Sparling et al, 2014), fruit orchards (Rosenbaum et al, 2012), rice cultivation (Attademo et al, 2014), soybean (Agostini et al, 2020;Dyck et al, 2021), maize and sorghum (Dyck et al, 2021), in addition to industrial use areas (Pollard et al, 2016) and water bodies with controlled spraying of pesticides (Thompson et al, 2004;Wojtaszek et al, 2005;Edge et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Among the main methodologies used to assess the effects of pesticides present in the environment, the survival and growth of tadpoles stand out (Thompson et al, 2004;Wojtaszek et al, 2005;Orton & Routledge, 2011;Edge et al 2014;Attademo et al, 2014;Sparling et al, 2014;Pollard et al, 2016;Agostini et al 2020;Dyck et al, 2021). In addition to these analyses, hatch success (Dyck et al, 2021), changes in mobility (Wojtaszek et al 2005;Agostini et al 2020), malformations (Thompson et al 2004), cytometry (Thompson et al, 2004), cell morphology (Attademo et al 2014) and biochemical markers such as carboxylase (Rosenbaum et al, 2012), cholinesterase (Attademo et al, 2014;Thompson et al, 2004), glutathione (Rosenbaum et al, 2012), and glutathione-Stransferase (Rosenbaum et al, 2012;Attademo et al, 2014) activities.…”
Section: Speciesmentioning
confidence: 99%
“…This may also be applicable for other mussel species with broad potential uses in freshwater mussel action plans, information campaigns and stream biotope conservation. Future studies should focus on long‐term exposure to assess the full impact of contamination (Belamy et al, 2020), and ex situ and in situ exposure can be combined to improve water quality testing for the conservation of aquatic species (ASTM, 2013a; Patnode et al, 2015; Pollard et al, 2017; Wagner et al, 2018). Caged experiments could be performed simultaneously with bivalve surveys (Nobles & Zhang, 2015; Patnode et al, 2015) to compare field‐deployed mussel results with wild populations.…”
Section: Discussionmentioning
confidence: 99%
“…In situ exposure with subsequent evaluation of species performance is often used in conservation biology (Armstead & Yeager, 2007 and references therein) and provides valuable information on the environmental quality and site suitability for endangered species (Haag, 2012;Pollard et al, 2017), including FPM (Buddensiek, 1995;Gum, Lange & Geist, 2011;Bílý et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation